ANALISIS KESALAHAN BERBAHASA PADA TATARAN SINTAKSIS DALAM PENULISAN TEKS DESKRIPSI PESERTA DIDIK KELAS V SD NEGERI FUIHIENG - Mathias Padamani; Yessy Mata; Yermia S. Wabang (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
The problem in this research focuses on the forms of syntactic errors made by students and the factors that cause them. This study aims to analyze Syntactic Language Errors in Writing Descriptive Texts by Fifth-Grade Students at the UPTD of Fuihieng State Elementary School. The method used is a qualitative descriptive method with data collection through documentation of student writing tests. The respondents in this study were 10 fifth-grade students. The research results indicate various forms of syntactic errors, including errors in sentence structure (subject, predicate, object), the use of conjunctions, and errors in the use of prepositional phrases. These errors are caused by students' lack of understanding of linguistic rules, the influence of regional languages, and a lack of practice in writing descriptive texts correctly. These findings are expected to provide input for teachers in improving Indonesian language learning, particularly in the writing aspect.